Sons e movimentos : sentidos do sagrado na musicalidade da folia de Santos Reis de Pirenópolis, Goiás - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
The Three Magic Kings’ Folia from Pirenópolis city takes place every year since 1986, from 26th to December 30 th and aims to worship the Three Magic Kings of the East and to collect donations to Saint Vincent Nursing Home, located on the downtown area of the city. The choosing of this Folia is justified by the fact of its celebration runs throughout both urban and rural zone, as well as it presents musical aspects to observation, for the selection of musicians from the nearby municipalities, congregating inside the Folia musical universe many different ways of playing and singing the Folia. The development of this search, started up from the proposal of revealing the senses of musicality in the celebrations to the Three Magic Kings. From a qualitative approach it was possible to extract the many different human experiences’ comprehensions and the explanations understood as the way of being in the world from those who participate in the Festival. The field researches were based on participative observation. The bibliographic search prioritized the inference of theorists who discusses the categories of sound landscape, Folia, ritual and music. The study of the Three Magic Kings’ Folia from Pirenópolis city approached by this search focus on the musicality present in the rituals and, for this, it was aimed to understand the senses and the meanings of the songs performed by the Foliões during the festive ritual course. The Folia in its itinerant movement is composed by the leaving, the Giro, the night out and the arriving; possesses many different landscapes which works as inspiration and are the harmonized by the lyrics sang forming the sound landscape from the festive space. The rituals build the rhythm of the festival, mark the steps in need to be executed and make sense for those who participate. And finally, the melodies intoned reveal the passing to the devotion state where the promises are accomplished and the godsend thanked. The presenting research is linked to the project: “Arts and Knowledge in Popular Catholic Manifestations” from the Goiás State University, supported by the Goiás State for Research Support Foundation – Fapeg, according to the public notice number 005/2012 which determined the Three Magic Kings’ Folias and the sung rosaries on the municipalities of Anápolis and Pirenópolis as subjects of studying.
Keywords: Folia de Santos Reis; Paisagem; Ritual; Musicalidade; Three Magic Kings’ Folia; Landscape; Ritual; Musicality; CIENCIAS HUMANAS::SOCIOLOGIA; GEOGRAFIA HUMANA::GEOGRAFIA URBANA; CIENCIAS HUMANAS::TEOLOGIA